2018
DOI: 10.1183/13993003.00860-2017
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory response to exercise in cardiopulmonary disease: the role of chemosensitivity and dead space

Abstract: The lungs and heart are irrevocably linked in their oxygen (O) and carbon dioxide (CO) transport functions. Functional impairment of the lungs often affects heart function and The steepness with which ventilation (') rises with respect to CO production (' ) ( the '/' slope) is a measure of ventilatory efficiency and can be used to identify an abnormal ventilatory response to exercise. The '/' slope is a prognostic marker in several chronic cardiopulmonary diseases independent of other exercise-related variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
83
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 118 publications
(174 reference statements)
4
83
2
4
Order By: Relevance
“…42 However, when the body is in a high coagulation state or when anticoagulation and brinolysis are weakened, thromboembolic diseases occur. 43 Thrombosis oen causes local blood coagulation in the vascular system, leading to health-related diseases including strokes and heart attacks. 44 Risk factors for thrombosis include abnormal hyperlipidemia, hyperglycemia elevated blood pressure and cancer.…”
Section: Anticoagulant Activity In Vitromentioning
confidence: 99%
“…42 However, when the body is in a high coagulation state or when anticoagulation and brinolysis are weakened, thromboembolic diseases occur. 43 Thrombosis oen causes local blood coagulation in the vascular system, leading to health-related diseases including strokes and heart attacks. 44 Risk factors for thrombosis include abnormal hyperlipidemia, hyperglycemia elevated blood pressure and cancer.…”
Section: Anticoagulant Activity In Vitromentioning
confidence: 99%
“…The V′E/V′CO 2 versus PaCO 2 plot may thus be more informative than VD/VTphys to differentiate pulmonary and extrapulmonary determinants of hyperventilation. As also discussed by WEATHERALD et al [3] it is important to avoid under-estimation or over-estimations of PACO 2 by PETCO 2 in patients with abnormal breathing patterns [3]. This problem is minimised by measuring P(a−ET)CO 2 at the anaerobic threshold.…”
mentioning
confidence: 98%
“…Excessive ventilation of high V′A/Q′ regions, or increased dead space ventilation does not affect PaCO 2 . However, as underscored by WEATHERALD et al [3], when both determinants of increased V′E/V′CO 2 coexist, quantifying the contribution of each is not simple.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for high indices of ventilatory inefficiency (V′E-V′CO 2 or the minimum ventilatory equivalent (V′E/V′CO 2 min)) to trigger uncomfortable respiratory sensations in cardio-respiratory disease has long been recognised [26,27]. More recently, several studies have demonstrated that a high ventilatory inefficiency is an early sign of impaired gas exchange efficiency (increased "wasted" ventilation) and/or excessive afferent stimuli to ventilation (as recently reviewed in [28]) as it is related to a high respiratory neural drive and dyspnoea in symptomatic smokers [29,30] and patients with mild COPD [31,32], heart failure [8], heart failure-COPD [33,34], ILD [35] and pulmonary hypertension (PH) [36,37]. Thus, the use of different indices of the V′E-V′CO 2 relationship has proved useful in the interpretation of CPET responses in patients with unexplained or disproportionate exertional dyspnoea [38].…”
Section: Introductionmentioning
confidence: 99%